The Supreme Court the personalities and rivalries that defined America - Rosen, Jeffrey 1964- (New York Times Books, 2007)
"The Supreme Court is the most mysterious branch of government, and yet it is at root a human institution, made up of very bright people with very strong egos, for whom political and judicial conflicts often become personal. In this character-driven history, Rosen recounts the history of the Court through the personal and philosophical rivalries on the bench that transformed the law--and by extension, our lives. Through these four rivalries, he brings to life the perennial conflict that has animated the Court--between those justices guided by strong ideology and those who forge coalitions and adjust to new realities.--From publisher description. Companion to the PBS series."--From source other than the Library of Congress
Also includes information on African Americans, Brown v. Board of Education, George W. Bush, Bush v. Gore, civil liberties, civil rights, conservatives, criminal procedure, Declaration of Independence, Democratic Party, Dred Scott v. Sandford, economic regulation, elections, executive (presidential) power, Federalist Party, federal (national) power, Fourteenth Amendment, Fourth Amendment, freedom of assembly, freedom of contract, freedom of religion, freedom of speech, Giles v. Harris, Gitlow v. New York, Griswold v. Connecticut, Hamdan v. Rumsfeld, Hamdi v. Rumsfeld, impeachment, judicial abstinence, judicial activism, judicial discretion, judicial independence, judicial politics, judicial restraint, judicial review, judicial subjectivity, judicial temperament, Ku, Klux Klan, labor law, liberals, Lochner v. New York, majority rule (majoritarianism), Marbury v. Madison, McCulloch v. Maryland, Miranda v. Arizona, New Deal, original meaning (originalism), Planned Parenthood v. Casey, Plessy v. Ferguson, pragmatism, right to privacy, racial discrimination, Ronald Reagan, Reconstruction Amendments, Republican Party (modern), Republicans (Jeffersonian), John Roberts, Roe v. Wade, Franklin D. Roosevelt, secession, segregation, stateʾs rights, Thirteenth Amendment, Clarence Thomas, U.S. Congress, U.S. Constitution, Earl Warren, etc.
A question of temperament -- The Virginia aristocrats : John Marshall and Thomas Jefferson -- The legacy of the Civil War : John Marshall Harlan and Oliver Wendell Holmes, Jr. -- Liberty and license : Hugo Black and William O. Douglas -- Two faces of conservatism : William H. Rehnquist and Antonin Scalia -- The future of temperament.
CSSP-6726 donated by The Rotary Club Beaverton, Oregon, United States of America.
Keywords: United States. -- Supreme Court -- History; Judges -- United States -- Biography; Judges -- United States -- History; Judges -- United States -- Psychology